Osteogenesis Imperfecta - A Case Series and Review of Recent Advances in Management - Ogundnare EO; AKintayo AA; Olatunya SO; Oluwayemi IO; Popoola SO; Atiba AS (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Osteogenesis Imperfecta (OI) is an uncommon congenital abnormality of the connective tissues in which diagnosis and management pose significant challenges especially in Low and Middle-Income Countries. The objective of this report is to draw attention to this uncommon congenital anomaly. Two cases of OI were seen at birth and managed in Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria. One of the babies died shortly after birth while the other baby was managed and discharged home. The discharged baby was on follow-up care in the clinic until the parents defaulted from further care. She eventually died at home after series of hospitalisations for recurrent respiratory tract infections. In conclusion, a high index of suspicion is required during prenatal care visit. When detected at birth, parents are to be educated on the multidisciplinary approach to management, challenges and possible outcome as there is yet no cure for this condition.